Reproduction, Globalization and the New War Against Women: Репродукција, глобализација и новата војна против жените - Federici, Silvia; Ruskovska, Rodna (Identities: Journal for Politics, Gender and Culture, 2016)
Author(s): Silvia Federici | Силвија Федеричи Title (English): Reproduction, Globalization and the New War Against Women Title (Macedonian): Репродукција, глобализација и новата војна против жените Translated by (English to Macedonian): Rodna Ruskovska | Родна Русковска Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 13, No. 1-2 (Winter 2016 - Summer 2017) Publisher: Institute of Social Sciences and Humanities – Skopje Page Range: 5-16 Page Count: 13 Citation (English): Silvia Federici, “Reproduction, Globalization and the New War Against Women,” Identities: Journal for Politics, Gender and Culture, Vol. 13, No. 1-2 (Winter 2016 - Summer 2017): 5-15. Citation (Macedonian): Силвија Федеричи, „Репродукција, глобализација и новата војна против жените“, превод од англиски Родна Русковска, Идентитети: списание за политика, род и култура, т. 13, бр. 1-2 (зима 2016 - лето 2017): 5-16.